2023
DOI: 10.7150/ijbs.83141
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 17 covalently binds to alpha-enolase and exacerbates proliferation of keratinocytes in psoriasis

Abstract: Dysregulated glucose metabolism is an important characteristic of psoriasis. Cytoskeletal protein keratin 17 (K17) is highly expressed in the psoriatic epidermis and contributes to psoriasis pathogenesis. However, whether K17 is involved in the dysregulated glucose metabolism of keratinocytes (KCs) in psoriasis remains unclear. In the present study, loss- and gain-of-function studies showed that elevated K17 expression was critically involved in glycolytic pathway activation in psoriatic KCs. The level of α-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Confirmation of these findings would imply that targeting CK-19 expression to inhibit cell proliferation could be a promising therapeutic strategy for psoriasis and its related conditions. These findings align with a cellular experiment on keratin-17, corroborating our understanding of keratin properties and functions ( 60 ). Although these observations suggest a potential involvement of CK-19 in immune processes and cell proliferation/apoptosis related to psoriasis and MASLD, the pathogenesis of CK-19 in these conditions is yet to be thoroughly reported.…”
Section: Discussionsupporting
confidence: 88%
“…Confirmation of these findings would imply that targeting CK-19 expression to inhibit cell proliferation could be a promising therapeutic strategy for psoriasis and its related conditions. These findings align with a cellular experiment on keratin-17, corroborating our understanding of keratin properties and functions ( 60 ). Although these observations suggest a potential involvement of CK-19 in immune processes and cell proliferation/apoptosis related to psoriasis and MASLD, the pathogenesis of CK-19 in these conditions is yet to be thoroughly reported.…”
Section: Discussionsupporting
confidence: 88%
“… [ 29 , 55 ] K17 Keratinocytes Anti-K17 therapy is an effective treatment option for psoriasis, and the K17 molecule, as a new target, may hold tremendous potential for the treatment of psoriasis in the future. [ 32 ] ENO1/K17 Keratinocytes Revealed the mechanism by which K17 interacts with ENO1 to promote glycolysis and proliferation of KCs, provides a new perspective for the study of the correlation between proliferation and metabolism. [ 35 , 36 ] STAT1/STAT3 JAK/STAT Keratinocytes Silencing STAT1 and STAT3 can inhibit the proliferation of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al demonstrated the interaction between KRT17 and ENO1 , which promotes glycolysis and proliferation in keratinocytes. 32 …”
Section: Targeting Keratinocytesmentioning
confidence: 99%
“…In vitro , montelukast demonstrated an inhibitory effect on M5-induced overexpression of factors associated with hyperproliferation (KI67, PCNA), inflammatory cytokines (IL-17A, IL-17F 34 , IL-6), angiogenesis (TGF-α 35 , VEGF 36 , and HIF-1α 37 ), keratogenesis (KRT16 38 , KRT17 39 , and cyclin E1 40 ), and autoimmunity (S100A12 41 , S100A15 42 , hBD-2 43 , and hBD-3 44 ) in HaCaT keratinocytes. The inhibitory effect of montelukast on HaCAT cell proliferation may be attributed to the modulation of the NF-κB signaling pathway in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%